Eunice Hunton Carter : A Lifelong Fight for Social Justice - Greenwald, Marilyn S; Li, Yun (Financial reporter) (Book collections on Project MUSE., 2021)
"The fascinating biography of Eunice Hunton Carter, a social-justice and civil rights trailblazer and the only woman prosecutor on the Luciano trial. Eunice Hunton Carter rose to public prominence in 1936 as both the only woman and the only person of color on Thomas Dewey's famous gangbuster team that prosecuted mobster Lucky Luciano. But her life before and after the trial remains relatively unknown. In this definitive biography on this trailblazing social justice activist, authors Marilyn S. Greenwald and Yun Li tell the story of this unknown but critical pioneer in the struggle for racial and gender equality in the 20th century. Working harder than most men because of her race and gender, Greenwald and Li reflect on Carter's lifelong commitment to her adopted home of Harlem, where she was viewed as a role model, arts patron, and community organizer, and later as a legal advisor to the United Nations, the National Council of Negro Women, and several other national and global organizations. Greenwald and Li show that Carter worked harder than most men because of her race and gender. They reflect on her lifelong commitment to her adopted home of Harlem, where she was viewed as a role model, arts patron, and community organizer, and later as a legal advisor to the United Nations, the National Council of Negro Women, and several other national and global organizations. Carter was both a witness and participant in many pivotal events of the early and mid 20th century, including the Harlem riot of 1935 and the social scene during the Harlem Renaissance. Using transcripts, letters, and other primary and secondary sources from several archives in the United States and Canada, the authors paint a colorful portrait of how Eunice continued the legacy of the Carter family that valued education, perseverance, and hard work: a grandfather who was a slave that bought his freedom and became a successful businessman in a small colony of former slaves in Ontario, Canada; a father who nearly single-handedly integrated the nation's YMCAs in the Jim Crow South; and a mother who provided aid to black soldiers in France during World War I, and who became a leader in several global and domestic racial equality causes. Carter's inspirational multi-decade career working in an environment of bias, segregation and patriarchy in Depression-era America helped pave the way for those who came after her"--